IMPLEMENTASI APLIKASI “PETANI” DAN “HUKAKU” DALAM UPAYA PENINGKATAN PENGETAHUAN TENTANG PRODUKTIVITAS DAN PENDAPATAN PERTANIAN SAMOSIR SUMATERA UTARA - Henny Febriana Harumy; Hanifah ZN. Amrul (LP4MK STKIP PGRI Lubuklinggau, 2018)
The problem that is carried out by farmers in Samosir is that it is difficult for them to sell their crops at a higher price. Apart from that, agricultural products have never been used. Usually, the farmer will turn on the waste or the rest of the production. Also, the problem that occurs is the attack of fungi on the onion plant. Until now there are no experts who can damage the farmers. Also, the question that arises is the attack of mushrooms on the onion plant. Until now there are no experts who can hurt the farmers. Solution to overcome this problem by using the